Equidad y regresividad, un estudio particular para el gravamen a los movimientos financieros en Colombia entre 1999-2018 (2020)
This research work makes a record of structure´s evolution of the levy on financial movements (GMF or four per 1000) in Colombia. The GINI and tax collection series are also presented. which will be used in the construction of the regression indicator and the productivity indicator for the tax with the aim of analyzing the efficiency and equity of the GMF in the system 1999-2018. The hypothesis arises that the tax four per 1000 or GMF complies with the principle of efficiency dictated by the Colombian Political Constitution in article 363 but does not comply with the principle of equity. The regressivity problem is that prevents the tax from complying with the two principles of taxation that the colombian constitution prosecutes. This work is based on primary sources from the archives of the Direction of National Taxes and Customs (DIAN), the National Administrative Statistics Department (DANE) and the World Bank.